INHIBITION CHARACTER ANALYSIS OF CORROSION INHIBITOR ON CARBON STEEL MATERIALS IN 1M HCL SOLUTION USING THE EIS METHOD - Rahayu Kusumastuti; Yustinus Purwamargapratala; Sofia Butarbutar; Sagino Sagino; Sriyono Sriyono; Abdul Hafidz (Badan Tenaga Nuklir Nasional, 2015)
Research on the effect of the concentration of the inhibitor on the corrosion behavior of carbon-steel material has been done. The research was started by immersing the prepared carbon-steel plate in a 1 M HCl en-vironment. After that, corrosion inhibitor was added with several concentrations, which are 0, 100, 200, 300, and 400 ppm in to that environment, to be stirred using a magnetic stirrer at 300 rpm for 30 minutes under room temperatur condition. The effect of the added inhibitor was then analyzed using the Electrochemical Impedance Spectroscopies (EIS) method. The experiment results showed that the greater the concentration of the inhibitor, the greater the resistance, so that the metal is more pro-tected from corrosion attack. The calculation results showed that the inhibitor efficiency is directly proportional to the concentration of inhibitor that is achieved at a concentration of 400 ppm with an efficiency of 71.24%.